Molecular Vanadium Oxides for Energy Conversion and Energy Storage: Current Trends and Emerging Opportunities. Issue 14 (17th December 2020) - Anjass, Montaha; Lowe, Grace A.; Streb, Carsten
Abstract: Molecular vanadium oxides, or polyoxovanadates (POVs), have recently emerged as a new class of molecular energy conversion/storage materials, which combine diverse, chemically tunable redox behavior and reversible multielectron storage capabilities. This Review explores current challenges, major breakthroughs, and future opportunities in the use of POVs for energy conversion and storage. The reactivity, advantages, and limitations of POVs are explored, with a focus on their use in lithium and post‐lithium‐ion batteries, redox‐flow batteries, and light‐driven energy conversion. Finally, emerging themes and new research directions are critically assessed to provide inspiration for how this promising materials class can advance research in sustainable energy technologies. Abstract : This Review critically discusses recent breakthroughs and future challenges in research on polyoxovanadate energy materials. The use of polyoxovanadates in batteries, redox‐flow batteries, light‐driven catalysis, and electrocatalysis is described together with an outlook on emerging themes and areas of future application.